2008
DOI: 10.1021/ma802006c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Branching and Gelation in RAFT Copolymerization of Vinyl/Divinyl Systems

Abstract: The reversible addition-fragmentation chain transfer radical polymerization (RAFT) with branching/ cross-linking is theoretically investigated on the basis of the method of moments. The system considered consists of the copolymerization of vinyl monomer in the presence of a small amount of divinyl comonomer. It is found that the gel point is significantly postponed by increasing the RAFT agent concentration. Flory's criterion, Fr w,0 ) 1, is found to be satisfied at the gel point in the RAFT cross-linking proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 61 publications
6
89
0
1
Order By: Relevance
“…S2; P2, P4, P6 and P8) which became significantly more separated with increasing concentrations of BMI in polymerization system. These results indicated the formation of microgelation or branched polymer structure, in agreement with previous reports which had observed these structures following the addition of divinyl monomer to living free controlled polymerization systems [64][65][66].…”
Section: Branched Azobenzene Copolymers By Raft Copolymerizationsupporting
confidence: 92%
“…S2; P2, P4, P6 and P8) which became significantly more separated with increasing concentrations of BMI in polymerization system. These results indicated the formation of microgelation or branched polymer structure, in agreement with previous reports which had observed these structures following the addition of divinyl monomer to living free controlled polymerization systems [64][65][66].…”
Section: Branched Azobenzene Copolymers By Raft Copolymerizationsupporting
confidence: 92%
“…We believed this reduction was caused by the increased possibility of the radical chain transfer and termination at the lower monomer/CTA ratio condition due to the higher chain/radicals density in small regions. It has been reported that the increased RAFT agent can significantly postpone the gel point [31][32][33] . Here, with the higher monomer/CTA ratio condition ([M] 0 :[CTA] 0 = 100:1), the molecular weight and distribution dramatically increased at the later reaction phase leading to the earlier gelation; in contrast this trend was significantly delayed with the lower monomer/CTA ratio (or in other words, with higher concentration of the RAFT agent) ( Figure 2C-D), which was consistent with the former studies.…”
Section: Effect Of Monomer/cta Ratio On Adjustable Polymeric Architecmentioning
confidence: 99%
“…Controlled/living radical polymerization (CLRP) techniques have been demonstrated to be advantageous in developing homogeneous polymer networks with controlled microstructure171819. However, since the CLRP methods generally require tedious pretreatment process prior to the immobilization of initiators on surface, it is difficult to directly apply them to inert polymeric substrates.…”
mentioning
confidence: 99%